Personal Data Protection to E-Commerce Consumer: What Are the Legal Challenges and Certainties? - Rahmi Ayunda (LAW REFORM, 2022)
Internet is one of the media facilities that is not only used for communication, but is also used in the process of buying and selling or trading (e-commerce). Behind all the conveniences obtained, e-commerce also raises the issue of consumer concerns on the responsibility for personal data. This study aimed to examine and re-explain the urgency of protecting personal data of e-commerce consumers and focused on the challenges and legal certainty of protecting personal data of e-commerce consumers in Indonesia. The method used was a doctrinal research method. This study showed that the application of data in e-commerce provides many benefits. However, the challenge was the absence of binding laws to safeguard personal data submitted to e-commerce companies. Legal certainty for the protection of e-commerce consumers is currently contained in several laws and regulations. Therefore, it is necessary to improve the effectiveness in the implementation of personal data protection and to regulate the protection of personal data in a law. In Indonesia, the urgency of the ratification of the Personal Data Protection Bill may become a solution in providing legal certainty for the protection of e-commerce consumers on their personal data.